High prevalence of overweight/obesity in adult persons with hemophilia in Utah and a review of the literature. Issue 8 (December 2020) - Lim, Ming Y.; Wei, Guo; Presson, Angela P.; Bray, Paul; Rodgers, George M.
Abstract : N/A: The objectives of this study were firstly to determine the prevalence of overweight/obesity in adult persons with hemophilia in Utah, and to explore the association between age, disease severity and race with body mass index (BMI), and secondly to provide recent data on the prevalence of overweight/obesity in the hemophilia population via a review of the literature. We conducted a retrospective cross section study of adult persons with hemophilia who were seen at a Utah hemophilia treatment center from 1 January 2017 to 31 December 2019. The electronic database PubMed was searched for studies with observation periods from 1 January 2012 to 31 December 2019. The age-adjusted prevalence for overweight/obesity in the adult Utah hemophilia population was higher than the overall Utah population and the general US population. After adjusting for race and age, mild hemophilia was associated with a 7.7% higher BMI (95% confidence interval, 0.023–15.98%, P  < 0.05). Review of the literature demonstrated high levels of overweight/obesity in hemophilia communities globally with considerable heterogeneity between studies. Despite increasing awareness, prevalence of overweight/obesity in the hemophilia population remains high in comparison with the general population. There is a critical need to address this issue acutely at hemophilia treatment centers due to the considerable burden of obesity. Abstract : Supplemental Digital Content is available in the text